My soul to take - Due, Tananarive, 1966- (Washington Square Press, 2011)
Bound to marry a murderous fellow immortal who is predicted to trigger an apocalypse, telepathic healer Fana works with the Life Brothers to eliminate disease throughout the world while struggling to escape her unwanted marriage.